Energy generation from water flow over a reduced graphene oxide surface in a paper–pencil device. Issue 18 (15th August 2016) - Arun, Ravi Kumar; Singh, Preeti; Biswas, Gautam; Chanda, Nripen; Chakraborty, Suman
Abstract : We report an ultra-low-cost device for energy conversion by exploiting the capillary flow of an electrolyte on a filter paper matrix in which a naturally deposited gradient of reduced graphene oxide is induced through chemical synthesis. Abstract : Energy generation using liquid movement over a graphene surface generally demands a very high rate of flow ( e.g. ∼100 ml min −1 ). In addition, a continuous flow of liquid is unable to generate a desired voltage, as it needs modification of the substrate such as development of nanopores and criss-cross network structures. Here, we report an ultra-low-cost yet highly efficient portable device for energy conversion, by exploiting the capillary flow of an electrolyte on a filter paper matrix in which a naturally deposited gradient of reduced graphene oxide is induced through chemical synthesis. In addition, the fibres and pores present in the paper offer a criss-cross network, acting as a natural splitter of a continuous flow into tiny droplets. Our methodology thus obviates the need for any elaborate procedure for pre-generation of droplets. Further, we fabricate the necessary electrodes on filter paper by simply scribing pencil tips on the same filter paper, which facilitates the necessary electrochemical reactions. Effectively, at the anode, electrons are released, which travel through the outer circuit for cation reduction at the cathode and deliver an electrical output (voltage/current), realizing the conversion of the chemical form of energy to the electrical form in the filter paper. An absorbent pad at the channel outlet ensures continuous flow of fresh solution in the device, resulting in an inexpensive platform for power generation over a prolonged period of time. A maximum current density of 325 mA cm −2 and a maximum power density of 53 mW cm −2 have been observed, which significantly outweigh the capabilities of other reported devices fabricated for similar purposes.